2005
DOI: 10.1073/pnas.0500062102
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant granulocyte colony-stimulating factor-transferrin fusion protein as an oral myelopoietic agent

Abstract: An expression construct harboring granulocyte colony-stimulating factor (G-CSF)-transferrin (Tf) fusion protein (G-CSF-Tf) was engineered by fusing human cDNAs encoding G-CSF and Tf to explore the feasibility of using Tf as a carrier moiety for oral delivery of therapeutic proteins. The recombinant protein, G-CSF-Tf, was harvested from protein-free, conditioned medium of transfected HEK293 cells. The in vitro studies demonstrated that the purified G-CSF-Tf fusion protein possesses the activity of both Tf recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 25 publications
7
94
0
1
Order By: Relevance
“…The method for plasmid construction was similar to that as described in the previous report (20). Human G-CSF cDNA harboring the signal peptide was cloned from human bladder carcinoma 5637 (American Type Culture Collection) by using RT-PCR.…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method for plasmid construction was similar to that as described in the previous report (20). Human G-CSF cDNA harboring the signal peptide was cloned from human bladder carcinoma 5637 (American Type Culture Collection) by using RT-PCR.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Furthermore, we have reported oral hypoglycemic activity of an insulin-Tf conjugate in diabetic rats (17,18), and oral myelopoietic activity of a G-CSF and Tf conjugate in BDF-1 mice (19). Most recently, we have produced a fusion protein from recombinant cDNA of G-CSF (20 kD) and Tf (80 kD) that possessed both transferrin receptor (TfR) binding ability in Caco-2 cells and the proliferative activity in NFS-60 cells (20). Furthermore, we have demonstrated that the G-CSF-Tf fusion protein can be absorbed across gastrointestinal epithelia, as indicated by its myelopoietic activity when orally administered in BDF-1 mice (20).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Meanwhile, the linker peptide facilitated both the independent folding of the SUMO and CVN subunits in the cytoplasm of E. coli and in the downstream purification process of LCVN (17). Direct fusion of functional subunits without a linker may lead to many undesirable outcomes including misfolding of the fusion proteins (18), low yield in protein production (19) or impaired bioactivity (20,21). Usually, PEG chemical conjugation step does not have good production efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been observed that Lf is relatively resistant to proteolysis in the gastrointestinal tract (Brock et al, 1976;Brines & Brock, 1983). Tf, which has similar properties with Lf, has been investigated for oral delivery of granulocyte colony stimulating factor (Bai et al, 2005), insulin (Shofner et al, 2010) and human growth hormone (Amet et al, 2010). However, Lf has not yet been reported as oral delivery vehicle.…”
Section: Introductionmentioning
confidence: 99%